HAM ANAK DALAM PENDIDIKAN - Lukman Arsyad (LP2M IAIN Sultan Amai Gorontalo, 2017)
Concept of children mobility still on expression unknown when it will be gladden reality. The all problem still regarded as a domestict problem and all it almost never become a serious isue, because it also never been thought as problem that must be reacted seriously. In reality today we can see indonesia children, they must live in unsuitable place for children improvement. The children are in unknown condition about their understanding and logical reasoning, they must live in traveling, isolation and must be a part of crime. That condition happen caused by high level poltical competition, it just to increase conflict escalation and will be ended by hardness.